Greenhouse Vegetable Market Development Based on the Supply Chain Strategy in the Republic of Uzbekistan - Sukhrob Rustamovich Umarov; Akmal Shaimardanovich Durmanov; Farida Beshimovna Kilicheva; Sherzodbek Murod ogli Murodov; Orifjon Boimurodovich Sattorov (International Journal of Supply Chain Management, 2019)
In the context of a need to expand the export potential of greenhouse vegetables of Uzbekistan, the goal of this research was to develop an approach to determining development strategies for greenhouse businesses in Uzbekistan on the international vegetable market. By means of correlation and regression analysis and a method of expert assessment, a system of indicators has been determined that quantitatively and qualitatively defines the competitiveness of Uzbek greenhouse businesses on the international vegetable market. A data array has been formed by standardized values of indicators for Uzbekistan in 2012–2018 aggregated annually (the time series was seven observations). The analytic hierarchy process by [1] and Fibonacci numbers have been used to develop models for comparative assessment of competitive advantages and to calculate an integrated index of countries’ competitiveness on the global greenhouse vegetable market. Based on the indices of competitiveness and world vegetable prices, a matrix of countries’ strategies on the international vegetable market has been formed. This matrix has testified that greenhouse businesses in Uzbekistan are positioned in a trade-off area with an overcharging strategy. The results obtained have allowed the authors to identify key threats to the sales of vegetables and to develop practical recommendations for expanding the export potential of greenhouse businesses in Uzbekistan on the international vegetable market.